Opportunities with low profilecross ventilated freestallfacilities - John F. Smith; Joseph P. Harner; Barry J. Bradford; M.W. Overton (Kansas Agricultural Experiment Station Research Reports, 2008)
Low profile cross ventilated freestall buildings are one option for dairy cattle housing. These facilities allow producers to control the cows' environment during all seasons of the year. As a result, an environment similar to the thermoneutral zone of a dairy cow is maintained during both summer and winter, resulting in more stable core body temperatures. Low profile cross ventilated facilities allow buildings to be placed closer to the parlor, thus reducing the time cows are away from feed and water. Other advantages include a smaller overall site footprint than naturally ventilated facilities and less critical orientation because naturally ventilated facilities should be orientated east to west to keep cows in the shade. Other benefits of controlling the cows' environment include increased milk production and income over feed cost, improved feed efficiency and reproductive performance, reduced lameness and fly control costs, and the ability to control lighting.; Dairy Day, 2008, Kansas State University, Manhattan, KS, 2008; Dairy Research, 2008 is known as Dairy Day, 2008
Keywords: Dairy Day; 2008; Kansas Agricultural Experiment Station contribution; no. 09-134-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1002; Dairy; Cross ventilated; Freestall facilities